The impact of drought on human capital in rural India - Joshi, Kuhu (Cambridge University Press, 2019)
We study the impact of a severe drought on children's educational outcomes in rural Maharashtra, a state in central India. Using pooled cross section data on children's test scores, we employ a difference-in-differences methodology to estimate the impact. We find that the drought caused a decline of 4.14 per cent in math scores and 2.67 per cent in reading scores of affected children. We also study heterogeneity in the impact by gender, age, parents' schooling, and household wealth, finding evidence in support of an income effect whereby households with limited means to smooth consumption disinvest in their children in response to the drought.